Pengembangan Media Scrapbook Materi Virus sebagai Suplemen Pembelajaran Kelas X SMA/MA Development of Virus Material Scrapbook Media as a Learning Supplement for Class X SMA/MA - Ulvaturrahmania Ulvaturrahmania; Relsas Yogica (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2022)
The success of the learning process is influenced by several factors, one of which is learning media. The media used must be varied and can increase students' learning motivation. The availability of media at SMAN 1 Nan Sabaris is less varied so that the learning that takes place is monotonous and affects students' interest in learning. Learning media can be used as a learning supplement to add or complement the weaknesses of pre-existing media. The purpose of this research is to produce a viral material scrapbook as a learning supplement for class X SMA/MA which is valid and practical. This research is a development research using the Instructional Development Institute (IDI) model. The research subjects were two biology lecturers, FMIPA UNP, one biology teacher at SMAN 1 Nan Sabaris, and 14 students in class X SMAN 1 Nan Sabaris. The object of this research is a virus material scrapbook as a learning supplement for class X SMA/MA. The research data are validity and practicality data. Based on the results of the study, the average validity result was 82.7% with a valid category and the average practicality result was 95.3% by teachers and 90% by students both in the very practical category. Based on this, it can be concluded that the virus material scrapbook media as a learning supplement for class X SMA/MA that was developed is valid and practical.